Functional horizontal gene transfer from bacteria to eukaryotes - Husnik, Filip; McCutcheon, John P (Nature reviews. Microbiology, 2018)
Bacteria influence eukaryotic biology as parasitic, commensal or beneficial symbionts. Aside from these organismal interactions, bacteria have also been important sources of new genetic sequences through horizontal gene transfer (HGT) for eukaryotes. In this Review, we focus on gene transfers from bacteria to eukaryotes, discuss how horizontally transferred genes become functional and explore what functions are endowed upon a broad diversity of eukaryotes by genes derived from bacteria. We classify HGT events into two broad types: those that maintain pre-existing functions and those that provide the recipient with new functionality, including altered host nutrition, protection and adaptation to extreme environments.
Keywords: přenos genů horizontální; regulace genové exprese; Eukaryota; fyziologická adaptace; Gene Expression Regulation; biologická evoluce; Biological Evolution; Bacteria; Gene Transfer, Horizontal; Adaptation, Physiological